2019
DOI: 10.1101/714071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biosynthesis of alkylcitric acids inAspergillus nigerinvolves both co-localized and unlinked genes

Abstract: Filamentous fungi are an abundant source of bioactive secondary metabolites (SMs). In many cases, the biosynthetic processes of SMs are not well understood. This work focuses on a group of SMs, the alkylcitric acids, each of which contains a saturated alkyl "tail" and a citratederived "head". We initially identified their biosynthetic gene cluster and the transcriptional regulator (akcR) involved in the biosynthesis of alkylcitrates in the filamentous fungus Aspergillus niger by examining the functional annota… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…In parallel to this study, BGC 34 ( Figure 3 ) was recently demonstrated to be responsible for alkyl citrate production in A. niger NRRL3 38 . For this SM class, a range of bioactivities has been reported, including antiparasitic 48 , antifungal 49 antibacterial 50 , and plant root growth promotion effects 51 .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In parallel to this study, BGC 34 ( Figure 3 ) was recently demonstrated to be responsible for alkyl citrate production in A. niger NRRL3 38 . For this SM class, a range of bioactivities has been reported, including antiparasitic 48 , antifungal 49 antibacterial 50 , and plant root growth promotion effects 51 .…”
Section: Resultssupporting
confidence: 75%
“…Schematic representation of BGC 34 and BGC 38 as predicted by antiSMASH. Based on sequence similarity and gene functional prediction, BGC 34 corresponds to the alkyl citrate-producing cluster identified in parallel to this study in A. niger NRRL3 38 . BGC 38 is positioned next to the azanigerone cluster.…”
Section: Resultsmentioning
confidence: 78%
“…The authors thank Dr. Marcos Di Falco for help with mass spectrometry, Thi Truc Minh Nguyen for providing Taxonomic tree of published Eurotiomycetes genomes. This manuscript has been released as a pre-print at Biorxiv (Palys et al, 2019).…”
Section: Data Availability Statementmentioning
confidence: 99%